Comparison of primary and secondary stability of a one-piece compressive conometric implant system in the posterior upper and lower jaws - Al-Hity, Thabat R.; El-Dhuwaib, Bilal; Al-Zahawi, Abdulsalam R.; Gul, Sarhang Sarwat (Frontiers in Oral Health, 2025)
BackgroundImplant stability plays a key role in establishing implant osseointegration and is a crucial factor in determining the appropriate timing for functional loading with a fixed prosthesis. This study aims to investigate the primary and secondary stability of a one-piece compressive conometric implant system in the posterior upper and lower jaws.Materials and methodsA total of 46 compressive one-piece dental implants (DIs) from ROOTT Trade Company were placed in the upper and lower jaws. Ready-made conometric TEC (titanium) with a prosthesis was fixed to the abutment. Implant stability was measured using an implant stability tester (AnyCheck device; NeoBiotech, Republic of Korea) by resonance frequency analysis (RFA) at facial, oral, mesial, distal, and occlusal surfaces. These measures were collected at baseline immediately after implant insertion, after 3 months, and at 6 months. The Kruskal–Wallis test was used to compare between the time points.ResultsIn total, 14 patients (8 men, 6 women; mean age 61.08 years; age range 35–79 years) were included. The median baseline RFA values show statistically significant differences between maxillary [55, interquartile range (IQR): 51–61] and mandibular (64, IQR: 60–67) as well as between men (59, IQR: 53–64) and women (67, IQR: 64–69). The occlusal surface shows the highest RFA compared to other surfaces. DI stability significantly increases in the maxilla and men after 6 months compared to the baseline (p = 0.0006 and 0.0001, respectively).ConclusionsThis study suggests that the one-piece compressive conometric implant system demonstrates reliable primary and secondary stability in the posterior upper and lower jaws, with a notable improvement after 6 months.